Beyond Egan’s supply chain management: advancing the role of logistics in the South African construction industry - Shakantu, Winston; Tookey, John; Muya, Manya; Bowen, Paul (University of the Free State, 2007)
The construction industry has globally been identified by investors and portfolio managers as under-performing in terms of return on investment (ROI), while simultaneously exposing the capital investment of investors to the highest levels of risk compared to any significant industry. In some cases, construction firms have received rates of return of as low as 1.5 to 2%. This is typically an unsustainable level of return for investors as they can gain a considerably higher ROI through much less risky financial vehicles such as gilts and bonds. Given such a low rate of return, the construction industry has for a number of years attempted to increase efficiency and reduce costs as a means of winning further business and increasing profitability. One of the methods that have been espoused as offering significant potential benefits for construction has been the industry-wide adoption of the principles of supply chain management (SCM). However, at present the bulk of SCM practice is focussed on high level strategic issues, whilst largely ignoring more operational issues related to logistics. This is a major omission, given the fact that a recent study by the Building Research Establishment (BRE) in the UK indicates that as much as 30% of the cost of construction is attributed to transportation of materials. This article examines, through a review of literature, the role of SCM in construction and the contribution an effective logistics system can make to increasing efficiency and reducing construction costs.

Die bou-industrie word wêreldwyd deur beleggers en portefeuljebestuurders vereenselwig met die onderprestasie van opbrengs op belegging. Terselfdertyd stel dit beleggers se kapitaalbelegging bloot aan die hoogste risikovlakke in vergelyking met dié van enige betekenisvolle ander nywerheid. In sommige gevalle verdien konstruksiefirmas opbrengste van slegs 1.5% tot 2%. Vir beleggers is dit ’n onvolhoubare vlak omdat hulle ’n veel hoër opbrengs deur veel laer risiko middele soos verbande en borgaktes kan verdien. As gevolg van hierdie lae opbrengs het die bou-industrie gepoog om doeltreffendheid te verbeter en kostes te beperk om sodoende verdere besigheid te genereer en winsgewendheid te verhoog. Een van die metodes wat uitstaan as ’n metode om betekenisvolle voordele vir konstruksie te bied is die industrie-wye aanvaarding van die beginsels van leweringskettingbestuur. Maar, tans is die omvang van leweringskettingpraktyk afgespits op hoëvlak strategiese kwessies terwyl die meer operasionele kwessies van logistiek ignoreer word. As in ag geneem word dat ’n resente studie deur die Building Research Establishment (BRE) in die verenigde koninkryk aandui dat soveel as 30% van konstruksiekoste aan vervoer toegeskryf kan word, is hierdie ’n groot weglating. Hierdie artikel ondersoek die rol van leweringskettingbestuur in konstruksie en die bydrae wat ’n effektiewe logistieke stelsel kan maak om doeltreffendheid te verbeter en kostes te sny.
Keywords: SCM; Supply chain management; Logistics; Process optimisation; Construction; Transportation